Study of Operating Parameters for Accelerated Anode Degradation in SOFCs1. Issue 4 (17th May 2017) - Ploner, A.; Hagen, A.; Hauch, A.
Abstract: Solid oxide fuel cell (SOFC) applications require lifetimes of several years on the system level. A big challenge is to demonstrate such exceptionally long lifetimes in ongoing R&D projects. Accelerated or compressed testing are alternative methods to obtain this. Activities in this area have been carried out without arriving at a generally accepted methodology. This is mainly due to the complexity of degradation mechanisms on the single SOFC components as function of operating parameters. In this study, we present a detailed analysis of approx. 180 durability tests regarding degradation of single SOFC components as function of operating conditions. Electrochemical impedance data were collected on the fresh and long‐term tested SOFCs and used to de‐convolute the individual losses of single SOFC cell components – electrolyte, cathode and anode. The main findings include a time‐dependent effect on degradation rates and the domination of anode degradation for the evaluated cell types and operating conditions. Specifically, the steam content as determined by fuel inlet composition, current density and fuel utilization was identified as major parameter, more important than for example operating temperature. The obtained knowledge is adopted to identify optimal operation profiles in order to acquire accelerated testing for lifetime investigation of SOFCs.